Frequency of ABO and Rh Blood Groups in Gastro Esophageal Reflux Disease - M Sadreddini (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: Gastro esophageal reflux disease (GRED) is one of the most common digestive disorders. The relationship between H. Pylori infection and blood groups has been demonstrated. Frequency of blood groups was investigated in many gastrointestinal diseases. Since there is no considerable information about the relationship between blood groups and gastroesophageal reflux, in this study we examine the frequency of ABO and Rh group system with gastroesophageal reflux.METHODS: In this analytic-descriptive study, patients with gastro esophageal reflux disease that attended in Urmia Imam university hospital digestive clinic after verifying the reflux (pyrosis three times a week for more than three months) enrolled in study and after determining age and sex referred to the laboratory for determining the ABO blood group and Rh factor. Collected data from the blood groups, Rh, age and sex convert to the numerical codes and compare with frequency of blood groups in west Azarbaijan. FINDINGS: In this study 175 patients, 92 male (52.6%) and 83 female (47.4%) have been studied. Mean age of patients was 39.14±12.99 years. Seventy two patients (41.1%) were A+, 2 (1.1%) patients were A-, 27 (15.4%) were B+, 3 (1.7%) were B-, 12 (6.9%) patients were AB+, 1 patient (0.6%) was AB with negative Rh and 49 patients (28%) were O+ and 9 patients (5.2%) were O- blood group. Among 34000 blood donors, 11216 (33.2%) was A+, 10219 (30.2%) was O+, 19% was B+, 7% was AB+ and 1% was AB-.CONCLUSION: This study shows there is a high frequency of A+ blood group in gastroesophageal reflux patients. According to these results there is no correlation between gastroesophageal reflux disease and ABO and Rh blood group systems.